Synergistic anti-tumor effects of bevacizumab and tumor targeted polymerized VEGF siRNA nanoparticles - Kim, Myung Goo; Jo, Sung Duk; Yhee, Ji Young; Lee, Beom Suk; Lee, So Jin; Park, Sung Gull; Kang, Sun-Woong; Kim, Sun Hwa; Jeong, Ji Hoon (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2017)
A variety of VEGF inhibitors have been reported to treat cancers by suppressing tumor angiogenesis. Bevacizumab, a monoclonal VEGF antibody, was the first FDA approved anti-angiogenic agent for cancer treatments. However, bevacizumab shows modest therapeutic efficiency and often cause resistant problem in significant populations of cancer patients. To solve these problem, we investigated the therapeutic efficacy of siRNA drugs targeting VEGF and combination of the RNAi drug with bevacizumab for cancer treatments. For efficient VEGF siRNA delivery, chemically polymerized siRNAs were complexed with thiolated-glycol chitosan (psi(VEGF)/tGC). The poly-VEGF siRNA and thiolated-glycol chitosan formed stable nanoparticles via electrostatic interaction and chemical crosslinking, and showed high accumulation in tumor tissues resulting in efficient gene silencing. Both VEGF siRNA nanoparticles and bevacizumab had efficient therapeutic effects in tumor xenograft mouse models. Interestingly, most pronounced therapeutic efficacy was observed when the two distinct VEGF inhibitors were treated in combination revealing synergistic effects. The results showed that the psi(VEGF)/tGC nanoparticle mediated knockdown of VEGF exerts anti-tumor effects and the combination treatments with bevacizumab can extend the treatments options to conventional bevacizumab treatments for cancer therapy. (C) 2017 Published by Elsevier Inc.
Keywords: ENDOTHELIAL GROWTH-FACTOR; INTRACRINE VEGF; CELLULAR UPTAKE; CANCER; ANGIOGENESIS; RESISTANCE; STABILITY; DELIVERY